2017
DOI: 10.1002/ptr.5912
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Curcumin Against Biofilm‐Producing Organisms on the Skin: A Review

Abstract: Turmeric root (Curcuma longa) is predominantly used as a spice, but has also long been known to possess antimicrobial, analgesic, antiinflammatory, and anticancer properties. One predominant group of active compounds in turmeric are curcuminoids, namely bright yellow-pigmented curcumin. While modern science has yet to fully investigate the therapeutic claims of turmeric and its derivatives, results have proven promising in decreasing pain and inflammation in arthritis, improving insulin sensitivity in diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Curcumin is widely used in medicine due to medicinal properties, cost-effectiveness, and simple extraction from a turmeric plant that grows in different regions in the world. Recent evidences have shown that curcumin possesses multiple biological activities and pharmacological properties including anti-inflammation (Dhir, 2018), antioxidation (Khanji et al, 2018), anticancer and antiproliferation (Barati, Momtazi-Borojeni, Majeed, & Sahebkar, 2019;Pan, Chen, Baek, & Zhong, 2018), antimicrobial (Marini et al, 2018), and free radical scavenger (Vaughn et al, 2017;Zhong et al, 2016). Some studies have suggested protective effects of curcumin against numerous diseases such as metabolic syndrome (due to improving insulin sensitivity, suppressing adipogenesis, reducing elevated blood pressure and decrease inflammation) (Ghazimoradi et al, 2017), inflammatory bowel disease (inhibit nuclear factor kappa-light-chain-enhancer of activated B [NF-κB], 5-lipoxygenase, and Toll-like receptor 4 (TLR-4)) (Singla et al, 2014), rheumatoid arthritis (due to regulating immune response and decrease the expression of cytokines and chemokine, (such as monocyte chemoattractant protein1 (MCP-1)) (Khayyal et al, 2018), cardiovascular disease (due to adjustment of the enzyme related to the metabolism of lipoproteins, decrease inflammation, and oxidative stress) (Li et al, 2019), and sepsis (due to modulate immune responses) (Chen, Lu, et al, 2018).…”
mentioning
confidence: 99%
“…Curcumin is widely used in medicine due to medicinal properties, cost-effectiveness, and simple extraction from a turmeric plant that grows in different regions in the world. Recent evidences have shown that curcumin possesses multiple biological activities and pharmacological properties including anti-inflammation (Dhir, 2018), antioxidation (Khanji et al, 2018), anticancer and antiproliferation (Barati, Momtazi-Borojeni, Majeed, & Sahebkar, 2019;Pan, Chen, Baek, & Zhong, 2018), antimicrobial (Marini et al, 2018), and free radical scavenger (Vaughn et al, 2017;Zhong et al, 2016). Some studies have suggested protective effects of curcumin against numerous diseases such as metabolic syndrome (due to improving insulin sensitivity, suppressing adipogenesis, reducing elevated blood pressure and decrease inflammation) (Ghazimoradi et al, 2017), inflammatory bowel disease (inhibit nuclear factor kappa-light-chain-enhancer of activated B [NF-κB], 5-lipoxygenase, and Toll-like receptor 4 (TLR-4)) (Singla et al, 2014), rheumatoid arthritis (due to regulating immune response and decrease the expression of cytokines and chemokine, (such as monocyte chemoattractant protein1 (MCP-1)) (Khayyal et al, 2018), cardiovascular disease (due to adjustment of the enzyme related to the metabolism of lipoproteins, decrease inflammation, and oxidative stress) (Li et al, 2019), and sepsis (due to modulate immune responses) (Chen, Lu, et al, 2018).…”
mentioning
confidence: 99%
“…Increasing body of literature supported the effects of curcumin in treating various wound types, and its great therapeutic potential (Mohanty & Sahoo, ; Tejada, Manayi, Daglia, et al, ; Vaughn, Haas, Burney, et al, ). For example, in a rat burn model, curcumin was found to attenuate injury progression as indicated by the proportion of necrotic unburned interspaces (Singer, Taira, Lin, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a phyto‐polyphenolic pigment extracted from turmeric ( Curcuma longa ) . It has been widely used for therapeutic purpose histologically due to the intrinsic anti‐inflammatory, antioxidant and antitumour properties . The extensive investigations and exploitations have characterized the wide‐spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] It has been widely used for therapeutic purpose histologically due to the intrinsic anti-inflammatory, [11,12] antioxidant [13] and antitumour properties. [14][15][16][17][18][19] The extensive investigations and exploitations have characterized the wide-spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth. [20][21][22][23][24][25] The various modes of action have been proposed underlying its therapeutic function in treatment of human cancer, including inhibition of proliferation, induction of cell apoptosis and suppression of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%